HUBUNGAN ANTARA KARAKTERISTIK DEMOGRAFI DENGAN STIGMA PUBLIK TERHADAP PENDERITA GANGGUAN JIWA DI DUSUN DEMEN KECAMATAN PAKEM SLEMAN YOGYAKARTA - Sulistyani, Enip Sekar; Pamungkas, Dewi Retno; Sutarjo, Puji (Media Ilmu Kesehatan, 2015)
Background: Mental disorders are t h e manifestations of deviant behaviors due to emotional distortion. Stigma is a distorted assessment that leads to isolation and ignorance of people with mental illness.Objectives: T o i n v e s t i g a t e t h e r e l a t i o n s h i p between demographic characteristics and public stigma tow a r d s people with mental disorders in Demen district, Pakem Sleman Yogyakarta.Methods: The study used descriptive correlation methods. The population in this study were all residents of Demen district, who aged >25 years. The sampling technique was cluster sampling with 200 respondents. Data were collected with a questionnaire. Analysis of the data used chi-square test and Kendall’s Tau.Results: There was no relationship between gender characteristics with public stigma towards people with mental disorders with p= 0.173 (p>0.05). There was a relationship between education level with the public stigma towards people with mental disorders with p= 0.016 (p<0.05). There was a relationship between socio-economic level with the public stigma towards people with mental disorders with p= 0.024 (p<0.05).Conclusion: There was a relationship between education and socio-economic level with public stigma towards people with mental disorders.Keywords: Demographic characteristics, stigma, mental disorders